Mechanical response of four polycarbonates at a wide range of strain rates and temperatures. (April 2023) - Song, Peihao; Trivedi, Akash R.; Siviour, Clive R.
Abstract: Polycarbonate is widely used in engineering applications in which its mechanical properties need to be well understood over a wide range of strain rates and temperatures. These properties can be dependent on the molecular structure. In this research, the thermomechanical properties of three homo-polycarbonates with different melt flow rates, and a modified co-polycarbonate, were extensively characterized to produce a large dataset of mechanical properties based on consistent thermal histories. Dynamic Mechanical Analysis was performed to obtain modulus data from which time-temperature superposition master curves were constructed. Quasi-static tensile tests were conducted at two loading speeds, using a digital image correlation system to calculate strain fields. Compression properties were measured at strain rates from 0.001 to 3000 s −1  at 20 °C, and from −60 to 120 °C at a constant true strain rate of 0.01 s −1 . The mechanical response of the polycarbonates is highly rate- and temperature-dependent, and the yield stresses at a wide range of rates and temperatures show time-temperature equivalence: the yield stress increases with an increase in strain rate or a decrease in temperature. Curves of yield stresses versus logarithm strain rate present an increasing gradient with increasing rate, which results from the secondary transition. Comparisons are drawn between time-temperature superposition parameters obtained from modulus data and from yield stress data, and between stress-strain curves obtained at different strain rates and at different temperatures. In the large strain region, apparent thermal softening can be observed during the medium rate tests, consistent with the transition from adiabatic to isothermal loading, whilst softening is less than expected at the higher rates. Graphical abstract: Image 1 Highlights: Compression tests performed on polycarbonates with different molecular weights and a co-polycarbonate from – 60 °C to 120 °C and 0.001 to 3000 s −1 . DMA and DSC performed to understand thermal properties. Time-temperature equivalence gave insights to the effects of molecular transitions and adiabatic heating on the mechanical response.